Variations of Ovitrap Autocidal Water for Controlling Aedes Aegypti - Syukra Alhamda; Yanti Cici Apriza; Nova Herawati; Debby Ratno Kustanto; Evi Susanti; Nurdin Nurdin; Harisnal Harisnal (Jurnal Kesehatan Masyarakat, 2025)
Dengue fever in Indonesia is still classified as a serious disease because it has increased yearly from 2011 to 2013. This study aims to determine the difference in the effectiveness of various types of water in the queue as a trap for eggs of Aedes aegypti mosquitoes in Bukittinggi. This type of research is experimental. The test used is the Anova test because the data is not normal using the Mann-Whitney test. The research sample used a sampling technique. This study uses primary data which can be seen from the number of trapped Aedes Aegypti mosquito eggs. The results showed that between the straw bales using well water and mineral water, the p-value was (0.421)> ɑ (0.05), meaning that there was no difference between the straw-soaked line with well water and water mineral. Meanwhile, after a statistical test was carried out between the straw bales using mineral water and rainwater, the p-value was (0.008)> ɑ (0.05), (Ho was rejected, Ha was accepted), meaning that there was a difference between the straw-soaked anthers and mineral water and rainwater. Based on the results of various types of attractants on the number of Aedes aegypti mosquito eggs trapped in the applied science laboratory of the University of Fort De Kock, Bukittinggi, the straw-soaked extract with rainwater is more effective because it produces more eggs than the extract soaked in straw with well water and extract soaked in straw with mineral water.